Vozes e memórias de um tempo em ruínas. Os regressos possíveis em O retorno de Dulce Maria Cardoso e O esplendor de Portugal de António Lobo Antunes - Silva, Suzana Costa da (2021)
This research aims to present, through the novels The Return by Dulce Maria Cardoso and The Splendor of Portugal by António Lobo Antunes, the ruins established by a historical moment, the independence of the Portuguese colonies in Africa, responsible for the displacement of thousands of people in the opposite direction of the navigation in the 15th and 16th centuries. The subjects of this time are marked by fragmentation, fluidity and disenchantment with the metropolis that barely welcomes them when they return from countries like, for example, Angola, referenced in the two works of this study. Focusing on these formerly colonizing subjects, wandering and marginalized by the condition of returnees – without being it –, we intend to analyze their narratives as a proposal of a production elaborated by individuals carried by the stigma of peripheral. Subjects silenced by the story of their return, in the novels, narrate their own experiences, especially though their biased memory. With the homeland in which they were born gone, these individuals remain uprooted, as a result of the postmodern condition, evidenced in the contemporary narratives represented here by Cardoso’s and Antunes’ novels. This non-belonging to any place further highlights the stigma of the subject in eternal displacement, the one who, without a place, neither adapts easily to any place, nor creates affective and lasting bonds. In this research, two families are taken as basis to represent the disintegration and fluidity of troubled times. Two characters named Rui, coincidently or not, in family structures ruined by loss or resentment, will be analyzed from the perspective of the present tense of the verb, in which life in Portuguese lands simply collapses. For different reasons, the two families of settlers look towards the past, including good and bad events experienced in Africa, as a way of invalidating the time and the decadent life to which they are exposed. Ruins, in the narrative of modern or postmodern molds, symbolize, above all, the empire undone in this great epic upside down